Region-Specific Reduction in Entorhinal Gamma Oscillations and Parvalbumin-Immunoreactive Neurons in Animal Models of Psychiatric Illness - Cunningham, Mark O. (J Neurosci, 2006)
Psychiatric illnesses, particularly schizophrenia, are associated with disrupted markers for interneuronal function and interneuron-mediated brain rhythms such as gamma frequency oscillations. Here we investigate a possible link between these two observations in the entorhinal cortex and hippocampus by using a genetic and an acute model of psychiatric illness. Lysophosphatidic acid 1 receptor-deficient (LPA1-deficient) mice show psychomotor-gating deficits and neurochemical changes resembling those seen in postmortem schizophrenia studies. Similar deficits are seen acutely with antagonism of the NMDA subtype of glutamate receptor. Neither model induced any change in power or frequency of gamma rhythms generated by kainate in hippocampal slices. In contrast, a dramatic decrease in the power of gamma oscillations was seen in superficial, but not deep, medial entorhinal cortex layers in both models. Immunolabeling for GABA, parvalbumin, and calretinin in medial entorhinal cortex from LPA1-deficient mice showed an ∼40% reduction in total GABA- and parvalbumin-containing neurons, but no change in the number of calretinin-positive neurons. This deficit was specific for layer II (LII). No change in the number of neurons positive for these markers was seen in the hippocampus. Acute NMDA receptor blockade, which selectively reduces synaptic drive to LII entorhinal interneurons, also disrupted gamma rhythms in a similar manner in superficial entorhinal cortex, but not in hippocampus. These data demonstrate an area-specific deficit in gamma rhythmogenesis in animal models of psychiatric illness and suggest that loss, or reduction in function, of interneurons having a large NMDA receptor expression may underlie the network dysfunction that is seen.